Wandering spleen with torsion presenting as acute abdomen - Puneet Mittal; Ranjana Gupta (Wolters Kluwer Medknow Publications, 2018)
Wandering spleen is a rare condition resulting from laxity of the suspensory ligaments of the spleen which predisposes it to torsion. We present a 24-year-old female who presented with acute abdominal pain due to torsion of the wandering spleen.